Hadith-Based Ecological Education as a Recontextualization of Environmental Values in Contemporary Islamic Education - Arifuddin; Yahya, Muhammad; Hafid, Erwin (Pascasarjana UIN Alauddin Makassar, 2026)
This study examines and formulates the concept of Hadith-Based Ecological Education as a recontextualization of environmental values within contemporary Islamic education in response to the growing global sustainability crisis. Employing a qualitative approach through library research, the study analyzes classical and contemporary hadith literature using a recontextualization framework to explore their relevance to modern ecological challenges. The findings reveal that hadiths contain not only individual moral teachings but also comprehensive ecological ethical principles, including stewardship (amānah), balance (mīzān), moderation (anti-isrāf), compassion (raḥmah), and responsibility toward all living beings. These values provide a strong normative and spiritual foundation for environmental education. The study further demonstrates that the integration of hadith-based ecological values into curriculum development, pedagogical practices, and school culture can foster four interrelated dimensions: ecological literacy, ecological character, ecological responsibility, and ecological spirituality. Through this integration, Islamic education is positioned not merely as a transmitter of religious knowledge but as a transformative agent capable of cultivating environmentally conscious and ethically responsible learners. Moreover, the study argues that Hadith-Based Ecological Education complements the principles of Education for Sustainable Development (ESD) by integrating scientific knowledge, ethical commitment, and spiritual awareness. This model offers a holistic educational paradigm that strengthens environmental stewardship, promotes sustainable behavior, and contributes meaningfully to both contemporary Islamic education and the broader global sustainability agenda.